2010
DOI: 10.1590/s0365-05962010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Alterações ungueais nos pacientes portadores de insuficiência renal crônica em hemodiálise

Abstract: BACKGROUND: Chronic renal failure affects almost all the systems of the body, including the skin and appendages. The nail disorders most commonly found in patients with chronic renal failure are half and half nails, absent lunula and splinter hemorrhages. OBJECTIVES: To evaluate the spectrum and the frequency of nail disorders in patients with chronic renal failure submitted to hemodialysis and compare them with a paired sample from the general population. METHODS: A case-controlled study paired for gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It is likely that this change is more related to conditions imposed by CRF than to HD. In our study, the prevalence rate was as high as that found in Martinez MAR's study [18]. However, the absence of lunula can be seen in normal subjects, without any renal insufficiency [19].…”
Section: Discussionsupporting
confidence: 45%
“…It is likely that this change is more related to conditions imposed by CRF than to HD. In our study, the prevalence rate was as high as that found in Martinez MAR's study [18]. However, the absence of lunula can be seen in normal subjects, without any renal insufficiency [19].…”
Section: Discussionsupporting
confidence: 45%
“…Although this change may be seen in patients with no demonstrable systemic abnormality, it is noted most commonly in patients with chronic renal failure undergoing hemodialysis. Prevalence of half-and-half nail is reported to be 7.7–50.6% in this group [3]. The pathogenesis of this color change is not clear; some authors have reported melanin deposits in the nail plate and thickening in the capillary wall, but others have considered the whiteness of this disorder to be caused by excessive development of connective tissue between the nail and bone that reduces the quantity of blood in the subpapillary plexus [4, 5].…”
mentioning
confidence: 99%
“…2 The two most common nail disorders among ESRD patients on hemodialysis are absent lunula and Lindsay's nails. 3,4 Lindsay's nails, also known as half-and-half nails, were first reported by Bean 5 in 1964 in azotemia and later described and coined "half-and-half nails" by Lindsay 6 in 1967 in a series of 1500 patients with chronic kidney disease. Lindsay's nails are seen in 20%-50% of patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nail changes are common in chronic kidney disease, affecting more than 75% of hemodialysis patients 2 . The two most common nail disorders among ESRD patients on hemodialysis are absent lunula and Lindsay's nails 3,4 . Lindsay's nails, also known as half‐and‐half nails, were first reported by Bean 5 in 1964 in azotemia and later described and coined "half‐and‐half nails" by Lindsay 6 in 1967 in a series of 1500 patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%